Application of non-contact video quantitative measurement method in reservoir bank landslide monitoring - Li, Yang; Li, Jun; Pei, Junrui; Chen, Wenjun; Luo, Guangqiang; Xia, Gang (Frontiers in Earth Science, 2024)
The geological structure of the reservoir bank landslide is complex and intricate. After deformation and damage, it causes river blockage, surges, and loss of people's lives and property, posing a huge threat. At present, in academia and engineering applications, a large number of techniques such as inclinometers, rain gauges, and surface GNSS deformation monitoring are still used for monitoring landslides on reservoir banks. This type of monitoring method has the problem of "point to surface" which can easily lead to missed detection and reporting in some areas, some disaster points are close to water and steep, difficult to reach, and equipment installation is difficult. This work designs and implements a non-contact video quantitative monitoring system for surface deformation of geological disaster. By constructing a deep learning neural network, deformation area recognition and displacement quantitative calculation are achieved; By obtaining continuous images for a long time, draw the surface displacement-time curve, and output the surface deformation data and landform changes of the disaster. Meanwhile, this work explores the impact of different lighting conditions on the recognition results of target areas. This work can provide non-contact monitoring methods and dynamic warning support for large-scale monitoring of geological disasters. a long time, a time slice of surface deformation of the disaster body is constructed to quantitatively output the surface deformation data and landform changes of the disaster body. 删除[YANG LI]: article 删除[YANG LI]: , as well as the application of binocular vision technology in three-dimensional modeling of disaster bodies 删除[YANG LI]: study 删除[YANG LI]: 删除[YANG LI]: 字体: (默认)Times New Roman, (中文)宋体, 小四, 字距调整: 0 磅 设置格式[YANG LI]: Due to the steep slopes and installation conditions of some disaster bodies, there are constraints on their arrival and installation, especially in the case of bank collapse. Contact installation poses a high risk and is difficult to operate and maintain. For disaster areas where monitoring instruments are not installed, this type of method is often prone to false alarms.